Association between brain health outcomes and metabolic risk factors in persons with diabetes - Reynolds, Evan L.; Votruba, Kristen; Jack, Clifford R.; Beare, Richard; Reid, Robert I.; Preboske, Gregory M.; Waseta, Camille; Pop‐Busui, Rodica; Nelson, Robert G.; Callaghan, Brian C.; Feldman, Eva L. (Annals of clinical and translational neurology, 2023)
We performed a cross‐sectional study to determine associations between cognition and MRI‐derived brain outcomes, with obesity, diabetes duration, and metabolic risk factors in 51 Pima American Indians with longstanding type 2 diabetes (T2d) (mean [SD] age: 48.4 [11.3] years, T2d duration: 20.1 [9.1] years). Participants had similar cognition (NIH Toolbox Cognition Battery composite: 45.3 [9.8], p = 0.64, n = 51) compared to normative data. T2d duration, but not other metabolic risk factors, associated with decreased cortical thickness (Point Estimate (PE): −0.0061, 95%CI: −0.0113, −0.0009, n = 45), gray matter volume (PE: −830.39, 95%CI: −1503.14, −157.64, n = 45), and increased white matter hyperintensity volume (PE: 0.0389, 95%CI: 0.0049, 0.0729, n = 45).